The multilingual Balkan region - Petrović, Jelena (Monitor ISH, 2005)
The paper addresses the problem of language diversification in former Yugoslavia during the 1990's. The civil war, nationalist discourse, and hate speech helped to modify the history, culture, use of language/s, and, most importantly, awareness of the Other. The Serbo-Croatian or Croat-Serbian language was politically and szmbolically split into four: Serbian, Croatian, Bosnian/Bosniak, and the forthcoming Montenegrin. The process of diversification gave rise to many paradoxes, problems of realisation, as well as clashes of ideas in the local academic circles, which were fast suppressed. After the 1990's, the language policy began to adjust to the language situation, but problems and confusion about the language/s remain.
Keywords: Jugoslavija; Yugoslavia; jugoslovanski jeziki; jezikovna politika; sociolinguistics; sociolingvistika